DECRASE IN CEREBRAL BLOOD FLOW DURING MAXIMAL HANDGRIP ISOMETRIC CONTRACTION – A BRIEF REPORT (Kinesiology, 2022)
Findings of the studies on the relationship between isometric handgrip contraction and changes in cerebral blood flow (CBF) are contradictory. The aim of the study was to evaluate CBF changes during one minute of a maximal handgrip isometric contraction. Our main hypothesis was that the maximal handgrip test will cause a decrease in CBF related to the decrease in handgrip strength. The study protocol included a transcranial Doppler ultrasound measurement of middle cerebral arterial mean flow velocity (Vmean) with the concomitant measurement of the sustained maximal handgrip strength over a period of one minute in 12 healthy male subjects. The main findings indicate that a maximal handgrip exercise causes a significant decrease in cerebral blood flow that is slightly more prominent on the contralateral side. This decrease is accompanied by a significant but transient increase in heart rate and also by an important (16%) increase in mean arterial pressure. The maximal isometric contraction may result in an considerable decrease in cerebral blood flow that in certain cases may become even clinically relevant. In the light of our findings, we suggest that maximal isometric contractions should be better avoided as a therapeutic tool and that isometric exercises of intensities up to 60% of maximal voluntary contraction are better used.Key words: neurophysiology, muscle function, exercise prescription